Transcriptomic Profiling Reveals Altered Expression of Genes Involved in Metabolic and Immune Processes in NDV-Infected Chicken Embryos - Malarmathi Muthusamy; Kannaki T. Ramasamy; Sunday Olusola Peters; Srinivasan Palani; Vasudevan Gowthaman; Murali Nagarajan; Sivakumar Karuppusamy; Vasanthakumar Thangavelu; Thiruvenkadan Aranganoor Kannan (Metabolites)
Objective: The poultry industry is significantly impacted by viral infections, particularly Newcastle Disease Virus (NDV), which leads to substantial economic losses. It is essential to comprehend how the sequence of development affects biological pathways and how early exposure to infections might affect immune responses. Methods: This study employed transcriptome analysis to investigate host–pathogen interactions by analyzing gene expression changes in NDV-infected chicken embryos’ lungs. Result: RNA-Seq reads were aligned with the chicken reference genome (Galgal7), revealing 594 differentially expressed genes: 264 upregulated and 330 downregulated. The most overexpressed genes, with logFC between 8.15 and 8.75, included C8A, FGG, PIT54, FETUB, APOC3, and FGA. Notably, downregulated genes included BPIFB3 (−4.46 logFC) and TRIM39.1 (−4.26 logFC). The analysis also identified 29 novel transcripts and 20 lncRNAs that were upregulated. Gene Ontology and KEGG pathways’ analyses revealed significant alterations in gene expression related to immune function, metabolism, cell cycle, nucleic acid processes, and mitochondrial activity due to NDV infection. Key metabolic genes, such as ALDOB (3.27 logFC), PRPS2 (2.66 logFC), and XDH (2.15 logFC), exhibited altered expression patterns, while DCK2 (−1.99 logFC) and TK1 (−2.11 logFC) were also affected. Several immune-related genes showed significant upregulation in infected lung samples, including ALB (6.15 logFC), TLR4 (1.86 logFC), TLR2 (2.79 logFC), and interleukin receptors, such as IL1R2 (3.15 logFC) and IL22RA2 (1.37 logFC). Conversely, genes such as CXCR4 (−1.49 logFC), CXCL14 (−2.57 logFC), GATA3 (−1.51 logFC), and IL17REL (−2.93 logFC) were downregulated. The higher expression of HSP genes underscores their vital role in immune responses. Conclusion: Comprehension of these genes’ interactions is essential for regulating viral replication and immune responses during infections, potentially aiding in the identification of candidate genes for poultry breed improvement amidst NDV challenges.